Block or Connect? Optimizing Ecological Corridors to Enhance the Dual Functions of Resistance and Provision in Forest-Mountain Ecological Security Barriers - Cao, Lei; Xi, Chengbin; Zhao, Xinyao; Zhang, Yunlu (Forests, 2025)
Ecological security barriers safeguard regional ecological security by blocking external risks and supplying internal services. However, existing research has primarily focused on optimizing the connectivity and protection of internal ecological patches within barriers. At a broader scale, there remains insufficient attention on coordinating the “blocking of external ecological risk corridors” and “connecting corridors that supply ecosystem services to internal urban areas”. To address this, this study develops a framework for constructing ecological corridors that integrates both reverse (resistance) and forward (provision) perspectives. Taking the Yanshan–Taihang Mountain Ecological Barrier as a case study, circuit theory is applied to identify risk corridors traversing the barrier area. Service supply corridors directed toward internal urban areas are also established, and key nodes along these corridors are identified. Furthermore, the XGBoost-SHAP method is employed to quantitatively analyze the influencing factors and mechanisms of these key nodes. Finally, strategies are proposed to block risk corridors and connect supply corridors. The main results are as follows: (1) A total of 29 risk corridors, 158 risk pinch points, and 210 risk barriers were identified, along with 250 supply corridors, 158 supply pinch points, and 118 supply barriers, revealing the distinct distribution patterns of both risk transmission and service supply corridors. (2) The dominant factors influencing different types of corridors exhibited significant differences: risk corridors were primarily regulated by natural factors such as mean annual evapotranspiration (EVA) and soil volumetric water content (VWC), whereas supply corridors were mainly influenced by human activities, including the human footprint index (HFP) and land surface temperature (TEM). (3) Even within the same type of corridor, the dominant factors and their operating mechanisms—such as threshold effects and nonlinear interactions—showed considerable heterogeneity across nodes of different characteristics. Based on these findings, differentiated policy recommendations were proposed. This study aims to synergistically enhance the bidirectional functionality of forest-mountain ecological barriers by disrupting external risk corridors and reconstructing internal supply networks. The framework and methodology presented here can provide theoretical and empirical references for the planning and management of other similar barrier regions.